Anions coordinating anions: analysis of the interaction between anionic Keplerate nanocapsules and their anionic ligands. Issue 7 (3rd February 2017) - Melgar, Dolores; Bandeira, Nuno A. G.; Bonet Avalos, Josep; Bo, Carles
Abstract : The interaction strength between Keplerates and anionic ligands depends on their p K a and solvation/desolvation effects. Abstract : Keplerates are a family of anionic metal oxide spherical capsules containing up to 132 metal atoms and some hundreds of oxygen atoms. These capsules holding a high negative charge of −12 coordinate both mono-anionic and di-anionic ligands thus increasing their charge up to −42, even up to −72, which is compensated by the corresponding counter-cations in the X-ray structures. We present an analysis of the relative importance of several energy terms of the coordinate bond between the capsule and ligands like carbonate, sulphate, sulphite, phosphinate, selenate, and a variety of carboxylates, of which the overriding component is contributed by solvation/de-solvation effects.